Influência de fatores geográficos na estimativa de evapotranspiração por modelagem, em área de transição planalto-pantanal do Cerrado - Vargas, Ursula Alejandra Salazar (2020)
The main objective of this study is to analyze the influence of local geographic factors on the performance of the sebal-based real evapotranspiration model (ETr) applied by the use of remote sensoring tools through Sentinel 2 satellite images in a region of the “Cerrado” considered transitional called Planalto- Depression. To make this possible first it was considered to evaluate if Sentinel 2 images have a satisfactory performance within the model to estimate the ETr calculation in the study area case to subsequently assess the influence of geographical characteristics such as land use, slope and climate on the performance of SEBAL model. The study area case is located within the Ribeirao Ponte de Pedra River bacia, in which 5 flow/meteorological stations called (A1, A2, A3, C1,C2) were installed. Their data were used for the calculation of (ETr). The stations are within a natural area where an intense exploitation of water resources can be observed over the years, either for agricultural use or for energy generation. It is necessary to mention that within the study area case there is an active PCH. This research sought to identify and justify the importance of the preservation of natural biomes such as the “Cerrado”, considering that severe alterations in natural vegetation could affect water resources. Studies currently show that plants maintain close relationships with the atmosphere and through their vital processes function as regulators of climatic conditions. The main climate regulatory process is evapotranspiration, by using energy for this process, plants decrease the amount of liquid radiation available to heat the air then deforestation or changes in natural vegetation could cause a decrease in evapotranspiration rates. It is important to emphasize that in the Planaltos is where some of the nascents of the tributaries that feed the main rivers such as the bacía of Upper Paraguay originat. To evaluate the SEBAL model a comparison of the results of (ETr) obtained from the combined FAO PENMAN MONTEITH 1998 and THORNTHWAITE & MATHER (1955) methods was compared with the results of (ETr) obtained from the model. This was done on the dates of 04/05/2018, 14/05/2019, 08/07/2018, 11/09/2018, 20/12/2018, 24/01/2019, and 25/03/2019. It was observed that the model has greater adaptation in the dry season (May-September) and within areas without slope or inclination with small vegetation. With the application of this model was sought to have a good approximation of the calculation of (ETr) in order to have better management and planning of the area's water resources considering the importance of maintaining natural vegetation otherwise could cause a loss of water over time and severely affect the water resources of the area as well as the water resources of the Pantanal Biome.